2016
DOI: 10.1002/pssc.201600248
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of semipolar (11‐22) AlGaN grown on m‐plane (1‐100) sapphire substrates

Abstract: Semipolar III‐nitrides have attracted increasing attention because of the reduced piezoelectric field in the active layer. In particular, (11‐22) plane is promising due to the small polarization field along the growth axis and the epitaxial matching on m‐plane sapphire. The aim of this study was to assess the effect of growth conditions on the structural and electrical properties of Si‐doped (11‐22) AlGaN. Semipolar AlGaN/AlN layers were grown on m‐plane sapphire by metal‐organic chemical vapor deposition at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…All XRD spectra showed the formation of almost single‐phase (11‐22) AlN, due to a high V/III ratio used for the AlN‐1 . The peak position of the (11‐22) reflection remained constant within the experimental resolution (≈0.01°), which indicates that the incorporation of Ga into (11‐22) AlN was negligibly small.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…All XRD spectra showed the formation of almost single‐phase (11‐22) AlN, due to a high V/III ratio used for the AlN‐1 . The peak position of the (11‐22) reflection remained constant within the experimental resolution (≈0.01°), which indicates that the incorporation of Ga into (11‐22) AlN was negligibly small.…”
Section: Resultssupporting
confidence: 80%
“…Thick (11‐22) AlN has been grown on m ‐plane sapphire by metal‐organic chemical vapor deposition (MOCVD) and molecular‐beam epitaxy . Recently, we have found that high‐temperature growth significantly improved the crystalline quality of (11‐22) AlN . The surface diffusion of Al adatom was enhanced at high temperatures, leading to the growth of high‐quality AlN layers.…”
Section: Introductionmentioning
confidence: 99%
“…After regrowth of AlN on the HTA-treated template, the surface morphology of (112̅2) AlN turns back to stripe features similar to that in the as-grown sample. No obvious difference in the surface morphology can be identified between Figure b,d, while the RMS roughness further reduces to 1.46 nm after AlN regrowth, smaller than the ever-reported values of heteroepitaxial AlN on m -sapphire. …”
Section: Resultsmentioning
confidence: 65%
“…In contrast, the high temperature (>1200 °C) is beneficial to promote the coalescence of AlN grains, and thus improve the quality of AlN film [ 6 ]. Moreover, some research groups have obtained high-quality semi-polar AlN in the high-temperature region, ranging from 1200 to 1650 °C [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Jo et al obtained smooth (11 2) AlN with a thickness of 2 μm by metal organic chemical vapor deposition (MOCVD) at 1500 °C [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some research groups have obtained high-quality semi-polar AlN in the high-temperature region, ranging from 1200 to 1650 °C [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Jo et al obtained smooth (11 2) AlN with a thickness of 2 μm by metal organic chemical vapor deposition (MOCVD) at 1500 °C [ 21 ]. Shen et al prepared the best quality semi-polar (10 3) AlN with NH 3 -free metalorganic vapor phase epitaxy (MOVPE) at a high temperature of 1650 °C [ 20 ].…”
Section: Introductionmentioning
confidence: 99%